Adult-onset phenylketonuria with rapidly progressive dementia and parkinsonism. Issue 3 (3rd May 2016) - Tufekcioglu, Zeynep; Cakar, Arman; Bilgic, Basar; Hanagasi, Hasmet; Gurvit, Hakan; Emre, Murat
ABSTRACT: Phenylketonuria (PKU) is an autosomal recessive metabolic disorder due to mutations in the phenylalanine hydroxylase (PAH) gene, which converts phenylalanine (PHE) to tyrosine. Although it is principally a childhood disorder, in rare cases, the first signs of PKU may develop in late adulthood resembling common neurological diseases. Here we report a 59-year-old, previously normal functioning man who was admitted with blurred vision, cognitive problems, and gait difficulty that began 8 months before. He had brisk reflexes and left side dominant parkinsonism. His Mini-Mental State Examination (MMSE) score was 25/30, and neuropsychological evaluation revealed a dysexecutive syndrome with simultanagnosia and constructional apraxia. His Clinical Dementia Rating score (CDR) was 1. Cranial MRI revealed bilateral diffuse hyperintense lesions in parietal and occipital white matter in T2, fluid-attenuated inversion recovery, and diffusion weighted images. Diagnostic workup for rapidly progressive dementias was all normal except PHE level which was found to be highly elevated (1075 μmol/L, normal 39–240 μmol/L) with normal tyrosine level (61.20 μmol/L, normal 35–100 μmol/L). Three months after PHE-restricted diet, his cognitive impairment and signs of parkinsonism significantly improved, with MRI scan unchanged. This case demonstrates that late-onset PKU is a rare, treatable cause of rapidly progressive dementia and parkinsonism with certain constellations such as consanguinity and white matter abnormalities (WMAs) in imaging.